(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the past 30 years, hearing aids have seen significant improvements, moving from basic analog sound processing methods to cutting-edge digital technology and Deep Neural Networks (DNNs) "on-the-chip" that provide real-time sound processing. Advanced hearing aids with DNN on-the-chip are more effective at making sounds audible as well as providing clearer understanding of speech in noise, improving recall, maintaining interaural loudness and timing differences, and enhancing the wearer’s capacity to selectively attend to the speaker of choice in difficult listening situations. These enhancements are given with extremely high sound quality and without acoustic feedback.